Empirical Analysis of Career Transitions of Sciences and Engineering Doctorates in the US - Natalia Mishagina (Queen's University, Department of Economics, 2007)
This paper studies career mobility of white male doctorates in natural sciences and engineering using the Survey of Doctorate Recipients (1973-2001). The paper focuses on two issues. First, it assesses the relevance of doctoral careers to sciences and engineering (S&E) in general, and research and development in particular. Second, it evaluates participation rates and mobility patterns of doctorates in careers of different types. To analyze how various factors affect mobility, a transition model with competing risks is specified and estimated. The paper finds that only half of doctorates have careers in R&D, and another 8% work in occupations outside the scope of S&E. Employment choices vary throughout a career. Mobility both within- and out of S&E is especially high during the first 16 years on the job. The effects of individual and job characteristics, research productivity, and labor market conditions on transitions are also assessed.
Keywords: C41; J24; J44; 330; duration analysis; competing risks; science and technology workforce; high-skilled labor; occupational choices; Karriereplanung; Berufswahl; Arbeitsmobilität; Ingenieure; Hochqualifizierte Arbeitskräfte; USA